Randomized comparison of cost‐saving and effectiveness of oral rapamycin plus bare‐metal stents with drug‐eluting stents: Three‐year outcome from the randomized oral rapamycin in Argentina (ORAR) III trial - Rodriguez, Alfredo E. (2012)
Objectives: The Oral Rapamycin in ARgentina (ORAR) III trial is a randomized study comparing a strategy of oral rapamycin (OR) plus bare-metal stent (BMS) versus a strategy of drug-eluting stents (DES) in patients with de novo coronary lesions. The purpose of this study was to assess the 3 years cost-effectiveness outcome of each strategy. Background: OR after BMS has been associated with reduction of target vessel revascularization (TVR) although its value in long-term efficacy in comparison with DES is unknown. Methods: In three hospitals in Buenos Aires, Argentina, 200 patients were randomized to OR plus BMS (n = 100) or DES (n = 100). Primary objectives were costs and effectiveness. Cost analysis included in-hospital and follow-up costs. Safety was defined as the composite of death, myocardial infarction (MI), and stroke. Efficacy was defined as TVR. Results: Baseline characteristics between groups were similar. The 3-year follow-up rate was 99%. Cardiac mortality was 2% and 5% in OR group and DES group, respectively (P = 0.44). The composite of death, MI and stroke rate was 11% in OR group and 20% in DES group (P = 0.078). TVR rate was 14.5% in OR group and 17.6% in DES group (P = 0.50), respectively. Three year cumulative costs were significantly lower in the OR arm as compared to the DES arm (P = 0.0001) and DES strategy did not result cost-effective according to the non-inferiority test. Conclusions: At 3 years follow-up, there were no differences in effectiveness between the two strategies, and DES strategy was not more cost-effective as compared to OR plus BMS.